EPISTEMOLOGI DAKWAH PERSPEKTIF KH. CHARIRI SHOFA - Sugeng Riyadi; Ahmad Luthfi Hamidi (Nizham Jurnal Studi Keislaman, 2021)
The study of the da'wah epistemology from the perspective of KH. Chariri Shofa reveals the concept of thoughts, struggles, masterpieces, and role-model aspects. This typical religious intellectual scholar with his magnum opus of the book "Al-Burhan" summarizes a number of brilliant achievements in the struggle from the local level of Banyumas to the national level. The comprehensive aspect of the da'wah of KH. Chariri Shofa covers literacy regarding Islamic laws, Islamic boarding schools, academic careers, da'wah methodology, and exemplary aspects in the family that inspires society. The climax was the appreciation for KH. Chariri Shofa obtained from the President of the Republic of Indonesia as the winner of the National Sakinah Family Competition in 2016. The epistemology of da'wah built by KH. Chariri Shofa includes the mastery of fundamental sciences in religious texts, especially Arabic language and isṭinbat al-hukmi, spiritual quality, Islamic social proress, and the strong academic capacity. The strongest aspect in the da'wah epistemology of KH. Chariri Shofa is on the scholar-intellectual capacity, role model, and the sympathetic and charismatic methodology of da'wah. The success indicators of the da'wah in the study of this figure are the acceptance of the society and the government, the scientific transformation and role model, and the inheritance of his eternal struggle.